A RELIABLE METHOD TO ANALYSE SOCIAL NETWORK SITES WITH INTERVIEWS - Tom, Sander,; Lee, Phoey; Biruta, Sloka, (European Scientific Journal, ESJ, 2015)
The paper determine the dimensions of social capital which has been described from Sander / Teh (Sander & Teh, 2014a). The dimensions can be used to measure and identify social capital in social network sites. The dimensions are formulated on a theoretical basis. The aim of the paper is to explore the use of social network sites by students and to identify parts of the social capital theory in social network sites under consideration of the framework. This paper use the results of 59 structured interviews with students analysed with a software to explore the behaviour of students in social network sites under consideration of the social capital theory. The second purpose for this paper is to use a method to analyse expert interviews as a qualitative method with a software. The software provides an objective perspective on the data as good as objective a method can be. This method can give critical feedback about an individual interpretation from a human researcher and new insights in the collected data. Further provides the method a reliable result for interviews as any replication provide the same result.